Arecaceae Plants (Palms) Used for Cultural Ceremonies in Acehnese Communities in Gandapura District, Bireuen Regency - Cut Roswita; Erlia Hanum; Tutiliana Tutiliana; Zainatul Hasanah; Nadia Aldyza (Research of Scientia Naturalis, 2024)
Ethnobotany is a branch of science that studies the relationship between humans and plants and their environment. Arecaceae is one of the most important plant families for human life and its species are widely used in everyday life, one of which is as a material for traditional cultural ceremonies. Plant parts that are utilized by the community consist of fruit and leaves. Acehnese people who live in Gandapura District still closely hold cultural customs traditions in all kinds of traditional ceremonies in the region but have not been widely developed about the introduction of cultural customs using arecaceae plants to modern society. This research is useful to provide information to modern society about the cultural customs of the community in the traditional use of Arecaceae plants. This research has been conducted by collecting data by distributing questionnaires, semi-structured interviews and free in-depth (open ended) in various age groups. The results showed 2 types of Arecaceae plants that are utilized by the community as cultural ceremonial tools, these types are: bak U (Cocos nucifera) and bak Pineng (Areca catechu).